Renal transplantation in HIV-positive renal transplant recipients: experience at the Mannheim University Hospital - Haas, Jenny; Singer, Thomas; Nowak, Kai; Göttmann, Uwe; Schnülle, Peter; Krüger, Bernd; Krämer, Bernhard; Benck, Urs Tobias (Transplantation proceedings, 2015)
Renal transplantation in HIV-positive patients with end-stage renal disease has in recent years become a successful treatment option. We report two patients who underwent renal transplantation using a combination of basiliximab, calcineurin inhibitors, mycophenolate mofetil (MMF), and steroids with a “non-interacting” antiretroviral combination therapy consisting of stavudine or abacavir, lamivudine, and nevirapine. We observed no acute rejection but a BK polyomavirus infection in both patients. In conclusion, a quadruple immunosuppression with an interleukin 2 receptor antagonist, a calcineurin inhibitor, MMF, and steroids appears to be advisable to prevent high rates of acute rejection, but if possible thereafter immunosuppression should be tapered rapidly (eg, MMF stop, prednisolone dose 5 mg/d). The selection of antiretroviral agents should avoid compounds that interact severely with the immunosuppression used.